2011
DOI: 10.1371/journal.pone.0025155
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Inhibition of Frontal-to-Parietal Feedback Connectivity Is a Neurophysiologic Correlate of General Anesthesia in Surgical Patients

Abstract: BackgroundThe precise mechanism and optimal measure of anesthetic-induced unconsciousness has yet to be elucidated. Preferential inhibition of feedback connectivity from frontal to parietal brain networks is one potential neurophysiologic correlate, but has only been demonstrated in animals or under limited conditions in healthy volunteers.Methods and FindingsWe recruited eighteen patients presenting for surgery under general anesthesia; electroencephalography of the frontal and parietal regions was acquired d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
174
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(198 citation statements)
references
References 42 publications
(46 reference statements)
20
174
3
Order By: Relevance
“…1). 13,14,18,19,21 The results of these studies are in line with earlier electrophysiological work in animals 22 and humans, 23 which demonstrated a loss of neural synchronization, under general anesthesia, between anterior and posterior parts of the brain. The work of John et al 23 is particularly noteworthy in this regard because they analyzed electroencephalography data from a total of 176 surgical patients anesthetized with a wide variety of pharmacological agents (induction of anesthesia with propofol, thiopental, or etomidate; maintenance of anesthesia with propofol, isoflurane, desflurane, or sevoflurane).…”
Section: " H Ow Do General Anesthetics Work?" In 2005supporting
confidence: 87%
See 3 more Smart Citations
“…1). 13,14,18,19,21 The results of these studies are in line with earlier electrophysiological work in animals 22 and humans, 23 which demonstrated a loss of neural synchronization, under general anesthesia, between anterior and posterior parts of the brain. The work of John et al 23 is particularly noteworthy in this regard because they analyzed electroencephalography data from a total of 176 surgical patients anesthetized with a wide variety of pharmacological agents (induction of anesthesia with propofol, thiopental, or etomidate; maintenance of anesthesia with propofol, isoflurane, desflurane, or sevoflurane).…”
Section: " H Ow Do General Anesthetics Work?" In 2005supporting
confidence: 87%
“…1). 13,14,18,19,21 The results of these studies are in line with earlier electrophysiological work in animals 22 …”
supporting
confidence: 88%
See 2 more Smart Citations
“…One such process is access of sensory information to consciousness (Dehaene and Changeux, 2011) as implied by the disrupted fronto-parietal connectivity during anesthesia-induced loss of consciousness (Ferrarelli et al, 2010;Ku et al, 2011), early (80-130 ms) synchronization correlates of conscious detection (Melloni et al, 2007;Wyart et al, 2012), and currently found correlations with BIT scores in patients. However, the targetrelated decrease of beta synchronization in control participants contradicts this explanation.…”
Section: Fronto-parietal Beta Synchronization During Visual Processingmentioning
confidence: 99%